Studi Mutasi Titik A3243G DNA Mitokondria Penyebab Maternally Inherited Diabetes and Deafness - Sriwidodo, Sriwidodo; Suprijana, O; Subroto, Toto; Maksum, Iman Permana (Majalah Ilmu Kefarmasian, 2008)
Point mutation of mitochondrial DNA A3243G has been known as a cause of Mater-nally Inherited Diabetes and Deafness (MIDD). Potency of MIDD can be identified from patient phenotype of Non Insulin Dependent Diabetes Mellitus (NIDDM). The objective of this study is acquiring information about MIDD on patient of NIDDM type and obtaining the simple method to detect the point mutation of mtDNA A3243G. 50 NIDDM patients were attained from RSCM Hospital, Jakarta. Information con-cerning family history with NIDDM and existences of deafness, medication, and other complication and manifestation were obtained through interview and ques-tioner. Point mutation of A3243G was determined with the method of PCR Allele’s Specific Amplification (PASA) Mismatch 2 bases and PCR-Restriction Length Poly-morphism (PCR-RFLP) with the HaeIIl restriction enzyme. Detectable Potency MIDD was found by perceiving the patient phenotype and identifying the mutation of heteroplasmic A3243G utilizing the PASA method.